(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This article aims to examine the apology for poetry by Philip Sidney. When studied in the history of Western literary criticism, Socrates starts and proceeds to Plato, Aristotle, Horace, Longinus and Quintilian, with whom classical critique stops. Then when the debate turns to English literary criticism, it starts with Sydney’s apology for poetry. In this early British literary critic, the fighter and writer try to protect poetry genre from the heartfelt assault on poetry and its purposes, Stephan Gossoon. His reasons are in accordance with Plato, who similarly told poets that his republic would be forbidden. Philip Sidney puts forth his strong arguments in favor of poetry and makes it very difficult to argue that poetry genres have second place in their beauty and grandeur to any other literary form. He tries to emphasize how poetry was successfully utilized as a vehicle for the transmission of ideas and points of view by the eternal geniuses. In that doing he says that poetry is superior to other knowledge areas.